Guidelines for the Clinical Management of HIV Disease - Orlander, Herbert (Caribbean Epidemiology Centre Port of SpainTT, 2000)
Provides a framework which will assist specialist clinicians, counsellors and psychologists to improve their skills in terms of management of HIV disease.